Paradigma Islam Tentang Kemiskinan Dan Solusi Pemecahannya - Moh. Subhan (Universitas Islam Lamongan, 2019)
Poverty is a complex and multidimensional problem because it relates to the inability of a person to access economics, politics, socio-culture, and participation in society. This phenomenon will never disappear from the face of the earth, although statistically the poverty rate can be minimized. The types of poverty are very much dependent on their perspective, there is relative poverty and absolute poverty. There are also natural poverty, cultural poverty, and structural poverty to minimize poverty can be done appropriately, when the factors causing poverty arise. Factors that cause poverty in general are internal, external and repressive theology. Naturally there is no human being who wants himself poor, because the poor conditions often make someone marginalized in his social life. Therefore, poverty must be eradicated and combated together to make humans dignified and protected materially and morally. Islam considers that poverty is not something that cannot be changed, therefore it is necessary to have tactical and strategic steps to make changes from poor conditions to being capable and dignified. To alleviate poverty, Islam has varied ways and alternatives, including reconstruction of theology of poverty, building collective awareness of eradicating poverty, and building an individual work ethic. Keywords: Islamic Paradigm, Islamic Solution, Poverty Minimization